Urban Land uses in Al-Thager District - Ghanem Yassin, Lect. Ali (Basra studies journal, 2024)
The research dealt with studying the uses of urban land in the Al-thagher district and how to distribute them using geographical information systems to identify the ability of urban institutions in the district to meet the needs of its residents . the study focused on the on the most important uses of urban land in the Al-thaghr district , which are residential , industrial , commercial , and religious institutoons in his research , the researcher used arc gis 10.8 and excel to analyze data